Analisis Penerapan Denda Pembiayaan Syariah Pada Federal International Finance (FIF) Group Di Kota Palangka Raya - Ahmad Fauzi; Tri Hidayati; Novi Angraeni (IAIN Langsa, 2022)
This research is motivated by the application of fines for late payments of murabahah financing installments at the FIF Group of Palangka Raya City. The focus of this research is how to apply sharia financing fines to the Palangka Raya City FIF Group and how to review Islamic law regarding sharia financing fines to the Palangka Raya City FIF Group. This research is included in empirical legal research with a legal sociology approach. The primary data in the study were obtained from interviews and documentation, and secondary data. The results of the research on the application of ta'zīr and ta'wīḍ fines are carried out if the customer is late in making installment payments that have fallen on a predetermined date. The fine for ta'zīr is Rp. 5,000.00 per installment and the amount of ta’wīḍ is calculated from the value of the loss calculated by the Credit Management Division of the Palangka Raya City FIF Group. However, the calculation of overhead costs and transportation costs is not clear, so AR, RU, and S customers object. Judging from Islamic law regarding sharia financing fines at the Palangka Raya City FIF Group based on sharia maqid (hifḍ al-mall/property) and the application of fines in murabahah financing, the fine contains benefits for each party. From the side of the Palangka Raya City FIF Group, it is so that customers do not experience payment problems, while from the customer side it is the purpose of imposing fines to discipline customers in carrying out their obligations. Although in the determination of ta’wīḍ there is uncertainty in the calculation of real losses related to overhead costs and transportation costs, so that customers object to it.